Reducing the humanitarian platform and the fundamental liberal democratic values : rise of the Hungarian anti-NGO endeavor - Elgabaili, Tiria (My University, 2020)
ÖZİNSAN PLATFORMLARIN VE TEMEL LİBERAL DEMOKRATİK DEĞERLERİN AZALTIMASI: MACARİSTANDA STK KARŞITI ÇABALARIN YÜKSELİŞİELGABAILI, TIRIAYüksek Lisans, Siyaset Bilimi ve Uluslararsı İlişkiler Anabilim DalıTez Danışmanı: Prof. Dr. Erhan Doğan2020Sovyetler Birliği'nin dağılmasından sonra, Macar hükümeti ile hükümet dışı kuruluşlar arasındaki ilişkilerde bazı değişiklikler oldu. Komünist dönemlerde (1949-1989), egemen bir sivil toplum örgütü oluşturulması yasaktı. Bağımsız bir üçüncü sektörün kurulması, demokratik dönemin başlangıcında ana endişelerden biri haline geldi. Bu tez, üçüncü sektörü ve kiliseler için ilk hükümet yardım sistemi olan “Bir ve Yüzde Bir” yasasını vurgulayarak Macar üçüncü sektörünün büyümesini analiz etmeyi amaçlamıştır.“Bir ve Yüzde Bir” yasasına göre, vergi mükellefleri yıllık vergi indirimlerinin yüzde 1'ini sivil toplum kuruluşları için, diğer yüzde 1’ini de kiliseler için ayırabilir. “Bir ve Yüzde Bir” yasası, komünizm sonrası zayıflamış bir sivil toplum içinde hükümet dışı alanı desteklemek için yeterli midir? Bu tez, Macar sivil toplumunda “Yüzde Bir” yasasının ortaya çıkışını ve uygulanmasını tartışmış ve sivil toplum örgütleri üzerindeki etkilerini araştırmıştır. Tez ayrıca, bu yasanın sivil toplumun hayırseverlik alışkanlıklarını nasıl etkilediğini de incelenmektedir. Bu tez, Macaristan'daki sivil toplum örgütleri, vakıflar ve dernek temsilcileriyle yapılan derinlemesine görüşmelerden, bu konudaki bilimsel çalışmalardan, vakıflar ve dernekleri kapsayacak bir biçimde arşiv verilerinden ve 1949'dan 2018'e kadar hükümet idaresinin tarihçesinden faydalanılarak yazılmıştır.iiBu tezde, halen maddi sorunlar yaşayan Macaristan üçüncü sektörünün gelişmesi için “Bir ve Yüzde Bir” yasasının yeterli olmadığı iddia edilmektedir. Bu mali desteğin alıcılarını vergi mükellefleri belirlese de, kaynak esas olarak hazineden gelmektedir. Bu nedenle Macar toplumunun, Macaristan'ın üçüncü sektörünün geliştirilmesine ve genişletilmesine daha fazla kaynak ayırması ve devleti de bu kaynakların hızlı ve eksiksiz bir biçimde sivil toplum kuruluşlarına ulaştırılması yönde zorlaması gereklidir. Sivil toplum örgütlerinin etkinliğini artırabilecek diğer unsurları belirlemek amacıyla daha fazla araştırmaya gereksinim bulunmaktadır.ContentsÖZ................................................................................................................................. iABSTRACT ................................................................................................................ iiiACKNOWLEDGEMENT .............................................................................................v1. INTRODUCTION..................................................................................................82. COMMUNIST HERITAGE OF CIVIL SOCIETY ............................................... 122.1 Introduction ....................................................................................................... 122.2 Communist effects on the institutional system .................................................... 132.3 Civil Participation in Nongovernmental Sector after the transition..................... 152.4 Initiative of Democratic Civil Society ................................................................ 172.4.1 Democratic institutional system .............................................................................. 212.5 Conclusion ......................................................................................................... 223. ONE AND ONE PERCENT LAW ....................................................................... 233.1 Introduction ....................................................................................................... 233.2 Decree of One Percent Law ................................................................................ 23 3.3 Reception of the One and One Percent Law ....................................................... 333.4 The Structure of Taxation................................................................................... 383.5 Role of the Government ..................................................................................... 423.6 Conclusion ......................................................................................................... 464. TECHNICAL USAGE OF ONE AND ONE PERCENT LAW ............................ 484.1 Introduction ....................................................................................................... 484.2 Overall legal context, the rights for associations, rights of foundations ............... 504.3 Eligibility for nonprofit status ............................................................................ 554.4 Eligibility for taxpayers ...................................................................................... 604.5 Duties and obligations of the tax authorities ....................................................... 634.6 Common rules of utilization ............................................................................... 684.7 Conclusion ......................................................................................................... 705. CURRENT RELATIONS OF THE HUNGARIAN THIRD SECTOR, CIVIL SOCIETY, AND THE GOVERNMENT ..................................................................... 71vii5.1 Introduction ....................................................................................................... 715.2 Civil Society after 1989...................................................................................... 725.3 Relations of the Hungarian Nongovernmental Sector and the State..................... 785.4 Conclusion ......................................................................................................... 866. CONCLUSION .................................................................................................... 87Bibliography ............................................................................................................... 89

ABSTRACTREDUCING THE HUMANITARIAN PLATFORM AND THE FUNDAMENTAL LIBERAL DEMOCRATIC VALUES: RISE OF THE HUNGARIAN ANTI-NGO ENDEAVORELGABAILI, TIRIAM.A., Department of International RelationsSupervisor: PROF. DR. ERHAN DOĞAN2020After the collapse of the Soviet Union, there were several changes between the Hungarian government and the nongovernmental institutions’ relationship. Under the Communist order, it was forbidden to create a sovereign civil society organization. The establishment of an independent third sector has become one of the main concerns at the beginning of the democratic era. This thesis aimed to analyze the growth of the Hungarian third sector, highlighting the “One and One Percent” law, which is the first governmental aiding system for the nongovernmental sector and the churches. According to the “One and One Percent” law, taxpayers can allocate one percent from their annual tax deductions to members of the nongovernmental sector and an additional one percent for churches. Is the “One and One Percent” law sufficient enough to supportivthe nongovernmental sphere within a weakened, post-Communist civil society? This dissertation discussed the emergence of Hungarian civil society and the implementation of the “One and One Percent” law within the Hungarian context and explored its effects on the nongovernmental sector. Additionally, it discusses how this law influences the philanthropic habits of the Hungarian civil society. The thesis was conducted secondary scholarly studies, archival data from Hungary about the nongovernmental organizations, including foundations, and associations and the history of the government administration from 1949 to 2018.The thesis argues that the “One and One Percent” law is not sufficient for the expansion of the Hungarian third sector, which still experiences financial and material deficits. Even though taxpayers determine the recipients of this financial support, the funding originates from the government’s aid framework. Therefore, it is essential to encourage civil society organizations to invest more in the progress and expansion of the Hungarian third sector by the state administration. Further research is needed to identify other factors that could promote the support of the nongovernmental sector.ContentsÖZ................................................................................................................................. iABSTRACT ................................................................................................................ iiiACKNOWLEDGEMENT .............................................................................................v1. INTRODUCTION..................................................................................................82. COMMUNIST HERITAGE OF CIVIL SOCIETY ............................................... 122.1 Introduction ....................................................................................................... 122.2 Communist effects on the institutional system .................................................... 132.3 Civil Participation in Nongovernmental Sector after the transition..................... 152.4 Initiative of Democratic Civil Society ................................................................ 172.4.1 Democratic institutional system .............................................................................. 212.5 Conclusion ......................................................................................................... 223. ONE AND ONE PERCENT LAW ....................................................................... 233.1 Introduction ....................................................................................................... 233.2 Decree of One Percent Law ................................................................................ 23 3.3 Reception of the One and One Percent Law ....................................................... 333.4 The Structure of Taxation................................................................................... 383.5 Role of the Government ..................................................................................... 423.6 Conclusion ......................................................................................................... 464. TECHNICAL USAGE OF ONE AND ONE PERCENT LAW ............................ 484.1 Introduction ....................................................................................................... 484.2 Overall legal context, the rights for associations, rights of foundations ............... 504.3 Eligibility for nonprofit status ............................................................................ 554.4 Eligibility for taxpayers ...................................................................................... 604.5 Duties and obligations of the tax authorities ....................................................... 634.6 Common rules of utilization ............................................................................... 684.7 Conclusion ......................................................................................................... 705. CURRENT RELATIONS OF THE HUNGARIAN THIRD SECTOR, CIVIL SOCIETY, AND THE GOVERNMENT ..................................................................... 71vii5.1 Introduction ....................................................................................................... 715.2 Civil Society after 1989...................................................................................... 725.3 Relations of the Hungarian Nongovernmental Sector and the State..................... 785.4 Conclusion ......................................................................................................... 866. CONCLUSION .................................................................................................... 87Bibliography ............................................................................................................... 89
Keywords: civil society; International relations; nongovernmental sector; One and One Percent Law; Political science; Post-Sovyet Macaristan; sivil toplum Post-Soviet Hungary; sivil toplum sektörü; Siyasal bilim; Uluslararası ilişkiler; Yüzde Bir Hukuk